Genetically determined dietary habits and risk of Alzheimer’s disease: a Mendelian randomization study - Teng, Fei; Sun, Jiahui; Chen, Zheyu; Li, Hao (Frontiers in Nutrition, 2024)
Background: Emerging evidence have suggested that dietary habits have potential implication on the development of Alzheimer's disease (AD). However, elucidating the causal relationship between specific dietary factors and AD risk remains a challenge. Therefore, our study endeavors to investigate the causal association between dietary habits and the risk of AD. Materials and methods: We analyzed data on 231 dietary habits sourced from the UK Biobank and MRC-IEU, and AD data obtained from the FinnGen database. Employing a framework based on the classic two-sample Mendelian randomization (MR) study, we utilized the inverse-variance weighted (IVW) method as the primary analysis. Additionally, we conducted Steiger filtering and other methods to mitigate horizontal pleiotropy. The robustness of our overall findings was confirmed through multiple sensitivity analysis methods, and forward MR and reverse MR to address potential reverse causality bias. Results: Our study evaluated the causal effect between 231 dietary habits involving over 500,000 participants of European ancestry, and 10,520 AD cases. Only oily fish intake demonstrated a significant protective causal relationship with AD following FDR correction (raw p-value = 1.28e-4, FDR p-value = 0.011, OR = 0.60, 95%CI: 0.47 - 0.78). Additionally, six dietary habits potentially influenced AD risk, with protective causal effects observed for average monthly intake of other alcoholic drinks ( p-value = 0.024, OR = 0.57, 95%CI: 0.35 - 0.93) and tea intake ( p-value = 0.047, OR = 0.78, 95%CI: 0.603 - 1.00). Conversely, detrimental causal effects were observed for the average weekly champagne plus white wine intake ( p-value = 0.006, OR = 2.96, 95%CI: 1.37 - 6.38), Danish pastry intake ( p-value = 0.036, OR = 13.33, 95%CI: 1.19 - 149.69), and doughnut intake ( p-value = 0.039, OR = 7.41, 95%CI: 1.11 - 49.57). Conclusion: Our results demonstrate oily fish intake had a significant protective causal relationship with risk of AD. Additionally, beneficial causal effects were observed with the average monthly intake of other alcoholic drinks and tea consumption. Conversely, average weekly champagne plus white wine intake, Danish pastry intake, and doughnut intake were causally associated with increased risk of AD.